SOCIO-POLITICAL SPEECH AND MILITARY PATRIOTIC SPEECH - Firuza Jalolovna Murodova (Western European Studies, 2024)
Speaking is the art of artistic speech, the science of speech that allows you toenjoy the incomparable power of the living word, make it beautiful, expressive andpersuasive. Editor's ChoiceAll Especially public speaking on socio-political topics is relevantfor each period and such speeches have been the main force influencing people's attitude tosociety. Our article considers the speech of military patriotism of a socio-political characterand its uniqueness
Keywords: Public Speaking; Culture Of Speech; Socio-Political Speech; Military Patriotic Speech; Gender Attitude